Further Evidence on the Distributional Effects of Disinflationary Monetary Policy - Willem Thorbecke (Levy Economics Institute of Bard College, 1999)
The performance of the U.S. economy between 1994 and 1998 was so good that some pundits began to call for the Federal Reserve to increase interest rates to depress economic activity and reduce asset prices. However, slowing the economy to stabilize asset prices would have adverse distributional effects. Impulse-response functions from identified vector autoregression (VAR) indicate that unexpected increases in the federal funds rate increase unemployment among blacks and Hispanics by 50 to 90 percent more than among whites. A narrative approach applied to two disinflationary periods shows that higher interest rates in the 1974 disinflation decimated the housing industry and that two interest-rate-sensitive sectors-construction and durable goods-showed the largest declines in 1980 and 1981 (periods following the 1979 tightening). Utilizing the Romer and Romer examination of the minutes of Federal Open Market Committee meetings to determine dates on which the Fed attempted to create a recession to reduce inflation, antiinflationary policy shocks can be estimated to increase unemployment among nonwhites more than twice as much as they do among whites. A social accounting matrix (SAM) indicates that in the sectors that were hardest hit by recession following the 1974-1975 and 1979-1982 disinflations (construction and durable goods), blue-collar workers were harmed more than other workers in terms of lost income and urban households were hurt much more than rural households. Minorities bear the brunt of disinflationary policy and do not share proportionately in the benefits of keeping the stock market stable, a factor that the Fed should take into account when contemplating actions aimed at stabilizing asset markets.
Keywords: 330